DINAMIKA BUDAYA DAN AGAMA (STUDI ANALISIS ATAS PENCARIAN NILAI-NILAI ISLAM DALAM KEBIJAKAN BUDAYA SUNDA MASA BUPATI DEDI MULYADI DI PURWAKARTA) - Anwar, Riyan Haqi Khoerul; Nurjaman, Andri; Yusuf, Muhamad (Scientia: Jurnal Hasil Penelitian, 2022)
This article discusses the dynamics of culture and religion in an analytical study of the search for Islamic values ​​in the Sundanese cultural policy of the regent of Dedi Mulyadi in Purwakarta. Dedi Mulyadi is a regent as well as a Sundanese culturalist, so in leading Purwakarta, he issued many policies based on Sundanese culture so that Purwakarta was well-known nationally and internationally. The purpose of this article is to analyze the search for Islamic values ​​in several Sundanese cultural policies during the regent of Dedi Mulyadi in Purwakarta. This article uses a qualitative research method which is a literature study. The data in this article were obtained from library sources such as books, scientific articles, and audio-visual sources of Dedi Mulyadi's interviews on Youtube, as well as sources that are certainly related to the object of research. The data obtained are presented in a narrative-descriptive manner. The data analysis technique used is the qualitative data analysis technique of Miles et al., namely data condensation, data presentation, and drawing conclusions. The results showed that the Sundanese culture-based policy of Dedi Mulyadi as the regent of Purwakarta had Islamic values ​​and teachings substantially and essentially. One example is in the sheathing of trees, purely for beauty and aesthetics, that beauty is upheld in Islamic teachings.